BATIK BANTEN: REPRESENTASI SEJARAH KEJAYAAN KESULTANAN BANTEN ABAD KE –XVII - Sulasiah Sulasiah (Universitas Sultan Ageng Tirtayasa, 2022)
Batik Banten is one of the contemporary batik which the design was taken from Reweng Trewengkal artifact (earthenware) of Banten Sultanate at XVII century. Then artifact design was adopted become Banten batik. Therefore, the aims of this research are to know the history of Batik Banten, to find the kinds of design of Batik Banten and how is it related to the history of Banten Sultanate. The method of this research is qualitative research with a historical approach. The step of this research are: choosing topic, heuristic, verification, interpretation and historiography. The result of this research are, first Banten had Batik Fabric since Sultanate era, it become special because Banten Batik is the only one batik in Indonesia which its design explain the history. The second, the total of various design of Banten Batik are 75 designs. It was taken from Reweng Trewengkal Artifact. The third, the various designs of Banten Batik explain the islamic glorious culture of Banten.Keywords: Banten Batik, Reweng Trewengkal artifact, Banten Glorious